Regulatory roles of long noncoding RNAs implicated in cancer hallmarks - Wang, Jun; Zhang, Xuan; Chen, Wen; Hu, Xiang; Li, Jing; Liu, Changning (International journal of cancer, 2020)
Cancer cells acquire numerous biological properties (designated “cancer hallmarks”), such as cell survival and energy metabolism, that facilitate tumor growth and metastatic dissemination during development. To date, eight hallmarks of cancer have been identified that provide a logical framework for understanding the remarkable diversity of neoplastic diseases, as proposed by Douglas Hanahan and Robert A. Weinberg. Long noncoding RNAs (lncRNAs), a category of transcripts widely demonstrated to exert significant regulatory effects on biological processes, have attracted considerable research attention due to their association with the occurrence and development of cancer. The mechanisms by which lncRNAs exert their functions require elucidation to optimize their potential utility as alternative biomarkers and therapeutic targets during tumor occurrence and progression. In this review, we have discussed recent research progress on lncRNAs involved in various cancer hallmarks and their related mechanisms of action, with a view to providing an updated picture of their immense therapeutic potential in the fight against cancer.